P04.23 Mind the gap! biological and behavioural concurrency and their potential for sti transmission in the british population. (13th September 2015) - Mercer, CH; Geary, R; Jones, KG; Clifton, S; Tanton, C; Sonnenberg, P; Gravningen, K; Johnson, AM
Abstract : Background: Key drivers for STI transmission are the number of sexual partners and their timing. Concurrent partnerships are a known risk factor but non-overlapping (serially monogamous) partnerships may be biologically concurrent for some STIs where infectious periods extend across the 'gap'. We examine recent partnership histories among people aged 16–44y in Britain and how they relate to reported STI diagnoses. Methods: Analyses of data collected for Britain's third National Survey of Sexual Attitudes and Lifestyles, a probability survey undertaken 2010–2012 with 9, 902 people aged 16–44y. Computer-assisted self-interviews included questions about participants' 3 most recent partners and STI diagnosis history. Gaps between partners were calculated from the dates of most recent sex with a former partner and first sex with the next partner. Results: Over 90% of men and women reported >=1 partners in the past 5y, of whom, 51.2% (men) and 42.5% (women) reported >=2 partners during this time and so had had >=1 gaps (total: 7, 724 gaps). The median gap was 2 months (IQR:-3 to 8 months) with two-thirds of all gaps >=1 month denoting serial monogamy. One-quarter (95% CI: 23.8%–26.2%) of all gaps were 0–3 months, while 21.8% (95% CI: 20.7%–22.9%) were >=12 months. In multivariable analyses which adjusted for total partner numbers (past 5y), reported STI diagnoses (past 5y) were as common among participants whose recent partners had been concurrent as serially monogamous participants where the gap was < = 4 months among men: 10.3% (95% CI: 7.6%–13.9%) vs. 11.3% (95% CI: 8.9%–14.3%), and < = 12 months among women: 12.3% (95% CI: 9.2%–16.3%) vs. 11.5% (95% CI: 9.7%–13.6%). Conclusion: While people in Britain have few partners on average and the majority with multiple partners are serially monogamous, the gap between partners is often shorter than the infectious period of common STIs and so effectively biologically concurrent. STI prevention efforts need to address this and should encourage STI testing prior to unprotected sex with new partners, even if serially monogamous. Disclosure of interest statement: AMJ has been a Governor of the Wellcome Trust since 2011. The other authors declare that they have no conflicts of interest.